Maskulinitas Dalam Iklan Extra Joss Energi Plus Nyali - Galih Dwi Wicaksana (Jurnal Ilmu Komunikasi, 2021)
Advertisement is a way to promoting products or services using the media as a channel. As a strategy for marketing products, advertisements often represent the products. Advertisements published in mass media, especially television, have the advantage of being able to display visuals and audio to their target audience. The masculinity that exists in energy drink advertisements can be seen from how the depiction of male figures, especially in Extra Joss advertisements ”Energi Plus Nyali” version which forms the image of male courage or virility. In this ad, there is no female figure at all. This is different from its competitor, Kuku Bima Ener-G, which still displays a female figure in its ad. This paper was conducted with the aim of explaining the representation of masculinity in the advertisement for the Energy Drink Extra Joss version of “Energi Plus Nyali” in forming an image of male courage or virility in heavy work done by men. This paper uses a type of research that is descriptive qualitative. with Roland Barthes' semiotic analysis who will analyze and read how the marking of masculinity appears in the advertisement for the Energy Drink Ekstra Joss version of ”Energi Plus Nyali”. From the results of the analysis, the aspect of masculinity in this advertisement can be seen from the use of symbolic images, especially in men with the type of hard worker, muscular, sweaty, and macho in the Extra Joss advertisement version of " Energi Plus Nyali". Coupled with the strengthening of aspects of masculinity because there are no female actors in the advertisement